The Interaction between Islamic Law and the Global Economic System - Haifsah Fikriah; Edi Suhara; Syafrita Huspika; Rahmi Jumiyah; Noorhani Dyani Laksmi (Insani: Jurnal Pranata Sosial Hukum Islam, 2026)
The interaction between Islamic law and global economics can no longer be understood merely as a process of normative adaptation to modern economic dynamics, but rather as an arena of epistemological dialectics that questions the legitimacy, ethics and fundamental orientation of contemporary global economic civilisation. This study aims to comprehensively analyse the dynamics of the relationship between Islamic law and the global economic system by highlighting the processes of integration, challenges, and opportunities for transformation that arise within it through a mixed-methods approach with a sequential exploratory design. The findings indicate that Islamic law, particularly through the reconstruction of values within maqāṣid al-sharī‘ah and its operationalisation in Islamic economics, possesses the capacity not only to adapt to the global economic system but also to offer substantive criticism of the dominance of the financial capitalism paradigm, which tends to generate inequality, speculation, and economic instability. In this context, instruments such as sustainable sukuk, zakat, and waqf serve as concrete representations of the integration of sharī‘ah values into modern economic governance oriented towards distributive justice, social inclusion, and sustainable development. The novelty of this study lies in a paradigm shift from a defensive-compatibility approach towards a transformative approach that positions sharī‘ah as a source of both normative and empirical innovation in building a more ethical and just global economic architecture. However, its implementation still faces challenges in the form of cross-jurisdictional complexities, limitations in the harmonisation of international regulations, and institutional resistance within a global economic system still dominated by neoliberal logic and financial capitalism.